2017
DOI: 10.1111/1460-6984.12336
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic changes in the speech of children with cerebral palsy following an intensive program of dysarthria therapy*

Abstract: Background: The speech intelligibility of children with dysarthria and cerebral palsy has been observed to increase following therapy focusing on respiration and phonation. Aims: To determine if speech intelligibility change following intervention is associated with change in acoustic measures of voice. Methods & Procedures:We recorded 16 young people with cerebral palsy and dysarthria (nine girls; mean age 14 years, SD = 2; nine spastic type, two dyskinetic, four mixed; one Worster-Drought) producing speech i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 54 publications
(116 reference statements)
1
22
0
Order By: Relevance
“…As louder speech is generated from increased breath support, the greater air volumes could also support longer utterances. The changes reported here are the perceptual correlates of the change in acoustic measures found in previous studies [9,[27][28][29]. The reports of children generalizing their new speech patterns to conversation outside the therapy environment and their articulation of strategies also suggest that motor learning has taken place and new behaviours can be produced when needed [13].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…As louder speech is generated from increased breath support, the greater air volumes could also support longer utterances. The changes reported here are the perceptual correlates of the change in acoustic measures found in previous studies [9,[27][28][29]. The reports of children generalizing their new speech patterns to conversation outside the therapy environment and their articulation of strategies also suggest that motor learning has taken place and new behaviours can be produced when needed [13].…”
Section: Discussionsupporting
confidence: 66%
“…Nevertheless, C6's parents described increases in her intelligibility in real life exchanges and greater communicative participation. Increases in intelligibility and participation without change in speech function have been observed in previous studies [11,27]. This lack of coupling between speech impairment and intelligibility suggests that the mechanism of change is more complex than an increase in speech function engendering increased intelligibility prompting increased participation, and that some other mechanism is at work.…”
Section: Discussionmentioning
confidence: 63%
“…2013, Pennington et al . 2010, 2013, 2018). As a result, speech–language pathologists in francophone environments have a weak research base from which to guide their treatment strategies for improving French‐speaking children's communication.…”
Section: Introductionmentioning
confidence: 99%
“…Most treatment studies on childhood dysarthria, with research advanced primarily by Pennington and colleagues (e.g., Pennington et al . 2018), target various subsystems to improve speech production. This research has found increased duration of breath groups, for example, following a subsystems‐based approach.…”
Section: Introductionmentioning
confidence: 99%
“…The finding of consistent change in speech development for children with SMI through the age of 7 years may have promising implications for treatment. Targeted therapies such as those employed by Pennington and colleagues (Pennington, Lombardo, Steen, & Miller, 2018;Pennington, Miller, Robson, & Steen, 2010;Pennington, Roelant, et al, 2013) that are specific to speech motor profiles, such as those identified by Allison (Allison & Hustad, 2018b), may be particularly beneficial when children are in periods of enhanced growth.…”
Section: Patterns Of Change Among Groupsmentioning
confidence: 99%